Groundwater: Quality Levels and Human Exposure, SW Nigeria - Olusola, Adeyemi; Adeyeye, Opeyemi; Durowoju, Olufemi (Journal of Environmental Geography, 2017)
Groundwater serves as a source of freshwater for agricultural, industrial and domestic purposes and it accounts for about 42%, 27% and 36% respectively. As it remains the only source of all-year-round supply of freshwater globally, it is of vital importance as regards water security, human survival and sustainable agriculture. The main goal of this study is to identify the main cause-effect relationship between human activities and the state of groundwater quality using a communication tool (the DPSIR Model; Drivers, Pressures, State, Impact and Response). A total of twenty-one samples were collected from ten peri-urban communities scattered across three conterminous Local Government Areas in Southwestern Nigeria. Each of the groundwater samples was tested for twelve parameters - total dissolved solids, pH, bicarbonate, chloride, lead, electrical conductivity, dissolved oxygen, nitrate, sulphate, magnesium and total suspended solids. The study revealed that the concentrations of DO and Pb were above threshold limits, while pH and N were just below the threshold and others elements were within acceptable limits based on Guidelines for Drinking Water Quality and Nigeria Standard for Drinking Water Quality. The study revealed that groundwater quality levels from the sampled wells are under pressure leading to reduction in the amount of freshwater availability. This is a first-order setback in achieving access to freshwater as a sustainable development goal across Less Developed Communities (LDCs) globally. To combat this threat, there is the need for an integrated approach in response towards groundwater conservation and sustainability by all stakeholders.